Comparison of physiological responses to morning and evening submaximal running - Martin, L.; Doggart, A. L.; Whyte, G. P. (Journal of Sports Sciences, 2001)
The aim of this study was to assess the effect of time of day on physiological responses to running at the speed at the lactate threshold. After determination of the lactate threshold, using a standard incremental protocol, nine male runners (age 26.3 +/- 5.7 years, height 1.77 +/- 0.07 m, mass 73.1 +/- 6.5 kg, lactate threshold speed 13.6 +/- 1.6 km x h(-1); mean +/- s) completed a standardized 30 min run at lactate threshold speed, twice within 24 h (07:00-09:00 h and 18:00-21:00 h). Core body temperature, heart rate, minute ventilation, oxygen uptake, carbon dioxide expired, respiratory exchange ratio and capillary blood lactate were measured at rest, after a warm-up and at 10, 20 and 30 min during the run. In addition, the rating of perceived exertion was reported every 10 min during the run. Significant diurnal variation was observed only for body temperature (36.9 +/- 0.9 degrees C vs 37.3 +/- 0.3 degrees C) and respiratory exchange ratio at rest (0.86 +/- 0.01 vs 0.89 +/- 0.07) (P < 0.05). Diurnal variation persisted for body temperature throughout the warm-up (37.1 +/- 0.2 degrees C vs 37.5 +/- 0.3 degrees C) and during exercise (36.2 +/- 0.6 degrees C vs 38.6 +/- 0.4 degrees C), but only during the warm-up for the respiratory exchange ratio (0.85 +/- 0.05 vs 0.87 +/- 0.02) (P < 0.05). The rating of perceived exertion was significantly elevated during the morning trial (12.7 +/- 0.9 vs 11.9 +/- 1.2) (P < 0.05). These findings suggest that, despite the diurnal variation in body temperature, other physiological responses to running at lactate threshold speed are largely unaffected. However, a longer warm-up may be required in morning trials because of a slower increase in body temperature, which could have an impact on ventilation responses and ratings of perceived exertion.